Zawadka: Zarys dziejów wsi, szkoły i sportu - Nowakowski, Andrzej (2024)
ZAWADKA: AN OUTLINE OF THE HISTORY OF THE VILLAGE, SCHOOL AND SPORTZawadka is a small village located in the Beskid Small region south of Wadowice. The village belongs to the administrative community of Wadowice in Wadowice county, in the voivodeship of Lesser Poland. It has about 800 inhabitants and the main occupation of the population is farming. The first unofficial record of the village dates back to 1419, and the next fully official one dates back to 1552. Until 1564 the village belonged to the duchy of Auschwitz and Zator, then called Silesian county.In the years 1772‑1918 the village was part of the Austrian Empire. During the period of reborn Poland (1918‑1939) tourism developed in Zawadka. The peak above the village called Bald Mountain has become a particularly popular place for excursions. Young Charles Wojtyła, later Pope John Paul II, visited this place many times together with his father and friends from Wadowice gymnasium. Both the First and the Second Wars painfully affected the inhabitants of the village. In the post‑war period, many residents of Zawadka found employment in the nearby industry and even in mining. Currently, many small businesses are developing in the village.The primary school in Zawadka was established around 1910. After the Second World War the school was moved to a new building in the centre of the village, which is currently being modernized (a sports hall is being built). This is primary school with 8 classes. In 2006 was named after general Walerian Czuma, who was associated with nearby Wadowice, and who was one of the main defenders of Warsaw in September 1939.In 1963 an archery sports club was founded at the local school and, except for a few short breaks, has been in existence to this day. Pupils and graduates of the school – young archers – achieve significant successes in regional and national competitions.
Keywords: Zawadka; Lesser Poland; outline; village history; local history